Acute Respiratory Distress Syndrome in a Carrier of an Interleukin-36 Receptor Antagonist Mutation With Generalized Pustular Psoriasis. Issue 1 (January 2022) - Baniel, Avital; Bar-Ilan, Efrat; Hilerowicz, Yuval; Merdler, Ilan; Shkury, Eden; Sarig, Ofer; Eskin-Schwartz, Marina; Sprecher, Eli
Background: Generalized pustular psoriasis of von Zumbusch is a rare variant of psoriasis often accompanied by systemic, sometimes life-threatening, symptoms. Generalized pustular psoriasis sometimes arises in pregnancy. Case report: A 31-year-old female, with a history of schizophrenia and recurrent episodes of gestation-associated pustular psoriasis, was admitted to our department because of a generalized pustular rash during the 22nd week of her fifth pregnancy. Clinical and histopathological examinations were suggestive of generalized pustular psoriasis (von Zumbusch type). During this hospitalization, she developed acute dyspnea, fever, tachycardia, and marked leukocytosis. An extensive workup failed to reveal an infectious, cardiac, or pulmonary abnormality, while severe respiratory distress necessitated mechanical ventilation. Radio-imaging revealed diffuse alveolar infiltrates consistent with acute respiratory distress syndrome (ARDS). In the absence of any other plausible cause, ARDS was considered as secondary to her skin disease. Genetic base was suspected, and genetic analysis uncovered a novel mutation in IL36RN encoding the IL-36 receptor antagonist. Only 15 cases of ARDS secondary to psoriasis have been described to date. This is the first report of this very rare complication in a known carrier of an IL36RN mutation. The fact that IL36RN is abundantly expressed in the lung as well as in the epidermis may underlie the unusual clinical features of this dramatic case. Conclusion: The present case suggests the need to carefully monitor patients with pregnancy-associated generalized pustular psoriasis for possible life-threatening pulmonary complications and the possible link to IL36RN mutation.